Challenging Bihar on Primary Education: Mother Tongue – ‘The Neglected Resource’ - Raaj, Shilpy (IJRDO- Journal of Educational Research, 2017)
The last few years have seen substantial and significant expenditure by the state governmentin primary education. There has been a concerted and accelerated attempt to fill huge glaringgaps in the provision of schooling that had accumulated over the last quarter of a century. Withina short period of time, over 3,00,000 teachers have been recruited, close to 1,00,000 newclassrooms have been built, textbooks are being delivered in time, and mid-day meals are beingserved in school.There have been special efforts made to enable girls across the state to continue in schoolpast the elementary stage. The state government has distributed bicycles to girls going tosecondary school. There are also special efforts to target the neediest children. All over the state,the very backward habitations have been identified. These habitations tend to be largelypopulated by “musahars” (one of the scheduled castes) or very backward minorities. Thegovernment’s concern with equity has led to targeted programmes being put into place to supportenrolment, attendance and learning of children in such habitations. Overall, many programmeshave been launched by the government to encourage children to go to school and stay in school.An example is the number of out of school children in Bihar. This is a key indicator ofchange. National and international goals for universalisation of elementary education put a greatdeal of emphasis on access and enrolment. In rural India, girls above 10 years are the hardest tobring into and keep in school. In 2005, in poor and educationally backward states, such as, Biharand Rajasthan, the proportion of girls in this age group who were not in school was well above20%. Across all states, from 2005 to 2010, Bihar has seen the sharpest decline in the proportionof children still not enrolled in school. The proportion of children out of school in Bihar hasdropped from 20.1% in 2005 to 6% in four years and now the numbers are below 5%. This is avery substantial achievement in such a short period of time. Bihar has come a long way towardsmeeting the target of universal enrolment.In 2004, in an average district in Bihar, the allocation of funds for activities under the SarvaShiksha Abhiyan (SSA), the government programme for universalising elementary educationwas around Rs 10 crore. By 2008, this number had risen to Rs 100 crore. According to theEconomic Survey of Bihar, in 2007-08, 67% of the state government’s social sector expenditurewas on elementary education. The survey also highlights Bihar’s expenditure of almost 20-25%of its total state budget on education.It is evident that there has been a massive infusion of inputs into the system at a very fastpace. Government expenditure on elementary education has increased enormously, basiceducational indicators, such as, access and enrolment are rising and the student-teacher ratios arebecoming more favourable. Compared to the situation that it had inherited, the currentgovernment has worked very hard to “catch up” and wipe out the back log of schoolingprovisions that had accumulated after years of neglect.